Cultural competence or deficit-based view? A qualitative approach to understanding middle school students' experience with culturally framed engineering - Khomson Keratithamkul; Justine N. Kim; Gillian H. Roehrig (SpringerOpen, 2020)
Abstract Background Recent policies have given momentum to the science, technology, engineering, and mathematics (STEM) education in the USA and throughout the world. This has resulted in rapid growth in engineering and STEM curricula, many of which incorporate global contexts to frame student experiences; however, little research has been done on the effects of this contextualization. Thus, it is critical to explore the impact of these curricula on student learning and the development of STEM identities, especially those who have historically been marginalized in STEM fields. The purposes of this study are to critically examine how STEM curriculum helps shape students' perceptions of the underlying cultural context and suggest ways that anti-oppressive education theory can be applied in middle school physical science classrooms. This study draws on classroom observational data and the curriculum text itself to understand how students perceive culture that they do not identify with. Results We found that the curriculum provides very limited perspectives of the non-dominant culture in which the learning was situated. Our results also indicate three emerging themes showing students to be demonstrating an elitist viewpoint, having a narrow view of another culture, or being indifferent toward the embedded cultural context in the lessons. As a class, deficit-based views of the people and places presented in the lesson were created rather than the desired culturally competent views. These negative perceptions were imprinted and solidified through limited portrayal of the embedded culture in the curriculum. Conclusions This work highlights the importance of curriculum context in students' learning. Beliefs about the people and places are created through global context presented in the curriculum. Portrayal of these people and places was not representative of the culture; thus, resulting in limited perceptions of the situated contexts. It is crucial that the teachers critically evaluate the curriculum prior to its implementation to make sure Others are represented appropriately by drawing upon the anti-oppressive education theory. Lastly, we also advocate for the incorporation of global culture in STEM curriculum by having students learn beyond what the written curriculum offers.